2020
DOI: 10.1101/2020.11.19.20234245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Validation and implementation of a direct RT-qPCR method for rapid screening of SARS-CoV-2 infection by using non-invasive saliva samples

Abstract: BackgroundThere is an urgent need to curb COVID-19 pandemic through early identification of asymptomatic but infectious cases. We aimed to validate and implement an optimised screening method for detection of SARS-CoV-2 RNA combining use of self-collected raw saliva samples, single-step heat-treated virus inactivation and RNA extraction, and direct RT-qPCR.Methods and findingsThe study was conducted in Sant Joan de Deu University Hospital (Barcelona, Spain), including: i) analytical validation against standard… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…In recent times, many studies have shown rapid molecular diagnosis of SARS-CoV-2 by omitting the standard RNA extraction step. 20 21 22 23 24…”
Section: Discussionmentioning
confidence: 99%
“…In recent times, many studies have shown rapid molecular diagnosis of SARS-CoV-2 by omitting the standard RNA extraction step. 20 21 22 23 24…”
Section: Discussionmentioning
confidence: 99%